Design of a multi-functional gel polymer electrolyte with a 3D compact stacked polymer micro-sphere matrix for high-performance lithium metal batteries. Issue 23 (30th May 2022) - Liang, Jiyuan; Tao, Runming; Tu, Ji; Guo, Chi; Du, Kang; Guo, Rui; Zhang, Wang; Liu, Xiaolang; Guo, Pingmei; Wang, Deyu; Dai, Sheng; Sun, Xiao-Guang
Abstract : A novel gel electrolyte with a 3D compact-stacked microsphere matrix is synthesized to realize long cycling stability of LMBs. Abstract : Lithium metal batteries (LMBs) are considered as promising high energy density batteries. However, they still suffer from poor cyclability due to the instability of solid electrolyte interphases (SEIs) and Li dendrite issues. Herein, a novel 3D densely packed multifunctional crosslinked gel polymer electrolyte (PHGPE) has been synthesized by in situ copolymerization of pentaerythritol tetraacrylate and 2-hydroxyethyl acrylate in a liquid electrolyte via a thermal initiation method. Due to intermolecular hydrogen bonding in the frameworks, the PHGPE exhibits a 3D compact-stacked and crosslinked micro-sphere structure, which benefits the construction of homogeneous Li + flux, enabling uniform Li plating/stripping and formation of robust SEIs onto the lithium electrode. Benefiting from the above advantages, symmetric Li cells in the PHGPE deliver excellent cyclabilities of 6000 h at a current density of 1 mA cm −2 (1 mA h cm −2 ) and 7700 h at 0.5 mA cm −2 (2 mA h cm −2 ). Moreover, the PHGPE has such a wide electrochemical window that it is compatible with both high-voltage LiNi0.8 Co0.1 Mn0.1 O2 and sulfur cathodes to realize long cycle life. Additionally, a LiFePO4 based pouch size LMB also presents promising performance. Therefore, this study of the PHGPE has opened a new avenue for high-performance LMBs with excellent versatility and practicality.